Self-Objectification and Cognitive Performance: A Systematic Review of the Literature - Winn, Lara; Cornelius, Randolph (Frontiers in Psychology, 2020)
Objectification theorists posit that exposure to sexually objectifying behavior, images, etc., leads women in particular to adopt an objectifying self-perspective. State self-objectification (SSO) (i.e., the internalization of the objectifying gaze) is theorized to usurp individuals' cognitive resources by diverting attention to their bodies. The objective of this paper is to systematically review the literature surrounding self-objectification and cognitive performance. Six databases retrieved 1,779 relevant articles. Studies were deemed eligible for inclusion if they (a) quantitatively investigated the relationship between SSO and cognitive performance using valid and reliable measures, (b) were published in a peer-reviewed journal between 1997 and 2019, inclusive, and (c) were available in English. Nine studies fulfilled all inclusion criteria. As the heterogeneity of the literature precluded meta-analysis, narrative synthesis was employed to review the results. While the quality of the studies was mixed, the results of our review support the contention that self-objectification impairs cognitive functioning. Appearance monitoring, actual-ideal self-discrepancies, negative self-conscious emotions, gender schema activation, and stereotype activation are evaluated as potential mechanisms behind the relationship between state self-objectification and cognitive performance, while chronic (trait) self-objectification is evaluated as a potential moderator.